The man in nursing : - Holtzclaw, Barbara J. (My University, 1981)
The study was designed to investigate factors that influence the man nurse's ability to negotiate role strain and possible status contradiction exerted by a feminine sex-typed profession. The following research questions were examined: Are men who choose nursing as a career less traditionally sex-typed and more androgynous than non-nurse men or women nurses? Is androgyny in men nurses associated with a more internal locus of control? Do traditionally sex-typed men nurses avoid role conflict by aligning their occupational role perceptions with their own sex-typed self-perceptions?

In a comparison with a large normative sample of non-nurse men, the expectation that men nurses would be more androgynous was not supported. Men nurses were not found more androgynous than women nurses, although women nurses tended to be more sex-typed. No differences were found between locus of control perceptions of androgynous subjects and those of other sex-role identities. Subjects of both genders and of various sex-role categories tended to view the nursing role as congruent with their own sex-typed self-perceptions.

Based upon Bandura's social learning theory, the theoretical framework of the study emphasized the mutual interaction of social shaping and reinforcements with cognitive and emotional factors in determining a man's view of the sex-appropriateness of an occupation. Drawing from Bandura's model of reciprocal determinism, it was expected that a man's selection of nursing as a career was in part related to this sex-role socialization; as well as his ability to cognitively and emotionally adapt his view of the profession.

Because the profession of nursing has been sex-typed by society as feminine, there has been considerable under-utilization of men in its ranks. Associated with this is a general avoidance of the field by men, with males constituting only slightly more than two percent of the nursing population.

The study sample consisted of twenty-six men and twenty-six women nurses, randomly selected from graduates of a large baccalaureate nursing program. Four study instruments were used: a biographical questionnaire, the Bem Sex-Role Inventory, the Ideal Nurse Survey (an adaptation of the Bem Inventory), and the Rotter I-E Locus of Control Scale.

While androgynous and undifferentiated self-perceptions appear to facilitate approach of men to a feminine sex-typed profession, the concept of androgyny needs more investigation before its influence on nurse-effectiveness can be established.
Keywords: Education, Health.